Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T21:31:36+01:00
A) (2x-3)-(x+5)+(x+4)=
=2x-3-x-5+x+4=
=2x+1

b) (3a-2)-(a+4)+(a-3)=
=3a-2-a-4+a-3=
=3a-9

c) 4(2y-7y²)-3(y²-3y)=
=8y-28²-3y²+9y=
=-31y²+17y

d) -5(2b+3z)+2(2b-4z)=
=-10b-15z+4b-8z=
=-6b-23z

liczę na naj


aha, tam, gdzie był np. -x i +x to się skracały...
1 1 1
2010-03-12T21:34:44+01:00
A (2x-3)-(x+5)+(x+4)
2x-3-x-5+x+4
2x-x+x=3-4+5
2x=8-4
2x=4 :/2
x=2

b (3a-2)-(a+4)+(a-3)
3a-2-a-4+a-3
3a-a+a=3+4+2
3a=9 :/3
a=3

c ) 4(2y-7y²)-3(y²-3y)
8y-28y²-3y²+9y
-31y²=-9y-8y :/-y
31y=17 :/31
y=31/17

d)-5(2b+3z)+2(2b-4z)
-10b-15z+4b-8z
-10b+4b=15z + 8z
-6b=23z :/-5
b=-23/5z
2 3 2